M. Smith, et al., Asia's New Industrial World, Methuen, Londres-Nueva York, 1985, 136 pp. - Hodara, Joseph (Estudios de Asia y África, 1987)
M. Uekusa y H. Ide, Industrial Policy in Japan, Pacific Economic Papers, 135, Australian National University, Canberra, 1986, 24 pp. J.D. Sachs, "External Debt and Macroeconomic Performance in Latin America and East Asia", en W. Brainard y G. Perry (eds.), Brookings Papers on Economic Activity, 2, Washington, 1985, pp. 523-576.